Acute hypervitaminosis a in a young lady - Khasru, MR; Yasmin, R; Salek, AK; Khan, KH; Nath, SD; Selim, S (Mymensingh Medical Journal, 2010)
Mymensingh Med J. 2010 Jul;19(2):294-8. The abstract of this article is available on the PubMed website